The Impact of Electromyostimulation on Strength, Recovery, and Performance in Soccer Athletes: A Systematic Review - Meng-Yuan Shu; Hyoung Suk Oh; Young-Jin Jo; Seon-Ho Eom; Jian Liang; Sang Mok Jung; Ki-Wan Kim; Joo-Ha Jung; Chae Woo Ma; Chul-Hyun Kim (Applied Sciences)
Soccer, as a high-intensity sport, places significant physical demands on athletes and is associated with a high risk of injury. Electrical muscle stimulation (EMS), a training and rehabilitation technology, has gained attention for its potential benefits in sports settings. This systematic review, conducted under the PRISMA guidelines, rigorously assessed the effectiveness of EMS in improving muscle strength, promoting post-exercise recovery, and facilitating injury rehabilitation among soccer players. A comprehensive search of the PubMed, Scopus, and Web of Science databases identified 10 studies meeting the inclusion criteria. Among these, six studies demonstrated a significant improvement in athletic performance following local or whole-body EMS application. Four studies provided evidence supporting EMS’s efficacy in enhancing post-exercise recovery and reducing recovery time after injuries, with observed reductions in recovery time. However, the majority of the included studies were not double-blind, which limits the strength of the evidence. None of the included studies reported EMS-related adverse effects. Overall, the current results suggest that EMS may be a useful adjunct to improve athletic performance and facilitate recovery in soccer players. This review offers actionable insights for coaches and athletes regarding the safe and effective application of EMS in soccer training and rehabilitation programs.